Design of a system for detection of non-ferromagnetic metallic foreign bodies based in eddy currents and GMI magnetometer - SEIXAS, VINÍCIUS T.; BARBOSA, CARLOS ROBERTO H.; Costa Monteiro, Elisabeth (Frontiers in Physics, 2024)
A portable magnetic mapping system was designed to determine the three-dimensional location of nonferromagnetic metallic foreign bodies to ensure fast and successful surgical procedures for their removal. The system is based on the induction of eddy currents in the foreign body by an excitation stage and the measurement of the magnetic field generated by these currents employing a commercially available high-resolution magnetometer based on the Giant Magneto-Impedance effect. The instrument topology is based on decoupling the excitation and measurement stages with a configuration that produces a high primary magnetic field in the foreign body region and a weak one in the GMI sensor region. This feature allows increasing the primary excitation magnetic field without saturating the GMI magnetometer, making it feasible to overcome relevant limitations evidenced in a previously developed instrument proposal. Computational simulations were built considering four possible configurations, with two models of excitation and two options for the magnetometer GMI sensitivity axis orientations. International guidelines for exposure limits to non-ionizing radiation and the principles of biometrology, besides constructive and electrical aspects, were also considered in the system design. The performance analysis of the most promising settings confirmed the viability of the proposed measuring instrument, optimizing the linear operation of the magnetometer during the measurement procedure and contributing to the construction of a complete measurement system prototype, with performance and safety characteristics ensured for the intended biomedical application.